Soil fertility, leaf nutrient concentration and yield limiting nutrients in oil palm (Elaeis guineensis) plantations of Surat district of Gujarat - BEHERA, BEHERA K; RAO, B N; SURESH, K; RAMACHANDRUDU, K; MANORAMA, K (The Indian Journal of Agricultural Sciences, 2016)
A survey was conducted for assessment of soil fertility status, leaf nutrient concentration and identification of yield limiting nutrients in twenty six oil palm (Elaeis guineensis Jacq.) plantations in Surat district of Gujarat. Soil pH, electrical conductivity (EC), organic carbon (OC), available potassium (K) (NH4OAc-K), available phosphorus (P) (Olsen-P), exchangeable calcium (Ca) (Exch. Ca) and magnesium (Mg) (Exch. Mg), available sulphur (S) (CaCl2-S) and hot water soluble boron (B) (HWB) content in surface (0-20 cm depth) and subsurface (20-40 cm depth) soil layers varied widely. Diagnosis and Recommendation Integrated System (DRIS) norms were established for different nutrient expressions and it was used to compute DRIS indices. As per DRIS indices, the order of requirement of nutrients in the area was found to be K > nitrogen (N) > B > P > Mg. Optimum leaf nutrient ranges as per DRIS norms varied from 2.63 to 2.85%, 0.16 to 0.18%, 0.56 to 0.88%, 0.34 to 0.84% and 9.10 to 32.5 mg/kg for N, P, K, Mg and B respectively. On the basis of DRIS derived optimum ranges, 65, 31, 35 and 8 per cent leaf samples had less than optimum concentration of N, P, K and B respectively. The optimum ranges developed could be used for efficient nutrient management.